2018
DOI: 10.3389/fmicb.2018.02828
|View full text |Cite
|
Sign up to set email alerts
|

Morin Protects Channel Catfish From Aeromonas hydrophila Infection by Blocking Aerolysin Activity

Abstract: Aeromonas hydrophila (A. hydrophila) is an opportunistic bacterial pathogen widely distributed in the environments, particular aquatic environment. The pathogen can cause a range of infections in both human and animals including fishes. However, the application of antibiotics in treatment of A. hydrophila infections leads to the emergence of resistant strains. Consequently, new approaches need to be developed in fighting this pathogen. Aerolysin, the chief virulence factor produced by pathogenic A. hydrophila … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Moreover, the increasing knowledge of structure and pore assembly of AerA makes it possible to clarify the mechanism of luteolin against the activity of AerA [48,49]. Our previous study confirmed that Arg356, Pro347 and Asn 37 were major binding sites of morin-AerA complex [18]. Here, we found that Asp7 and Asp311 were major sites when determined by the same methods with morin.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Moreover, the increasing knowledge of structure and pore assembly of AerA makes it possible to clarify the mechanism of luteolin against the activity of AerA [48,49]. Our previous study confirmed that Arg356, Pro347 and Asn 37 were major binding sites of morin-AerA complex [18]. Here, we found that Asp7 and Asp311 were major sites when determined by the same methods with morin.…”
Section: Discussionsupporting
confidence: 80%
“…According to previous study, AerA could lead to cell injury of a number of mammalian cells [ 28 ]. Our previous studies indicated that A549 and Vero cells could be used as target cells to evaluate the effects of natural compounds to AerA induced cell injury [ 18 , 19 ]. As shown in Figure 7(a ), untreated cells were shown green, indicating that cells were live.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of flavonoids and other small molecules from plants as anti-virulence agents has been reported previously and reader is directed to the excellent review by Wu et al [42]. Dong et al showed that the flavonoid morin, used in traditional Chinese medicine, directly inhibits the hemolytic activity of aerolysin, the primary virulence factor of A. hydrophila strains and protects catfish from A. hydrophila infection [43]. Eugenol, a constituent of clove oil, can inhibit quorum sensing in methicillin-resistant S. aureus (MRSA) clinical strains [44].…”
Section: Discussionmentioning
confidence: 99%